2015
DOI: 10.1182/blood-2015-01-621664
|View full text |Cite
|
Sign up to set email alerts
|

International phase 3 study of azacitidine vs conventional care regimens in older patients with newly diagnosed AML with >30% blasts

Abstract: Key Points• Azacitidine increased median overall survival by 3.8 months vs current commonly used AML treatments (10.4 vs 6.5 months; P 5 .1009).• Azacitidine safety in patients age $65 years with AML (.30% blasts) was consistent with its known safety profile in other trials.This multicenter, randomized, open-label, phase 3 trial evaluated azacitidine efficacy and safety vs conventional care regimens (CCRs) in 488 patients age ‡65 years with newly diagnosed acute myeloid leukemia (AML) with >30% bone marrow bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
875
6
19

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,039 publications
(946 citation statements)
references
References 25 publications
46
875
6
19
Order By: Relevance
“…In total 7 patients with MDS or CMML and 2 patients with AML receiving CC‐486 monotherapy in this study attained CR or PR, including, importantly, patients for whom previous DNMTi therapy had failed. While multiple studies have shown injectable azacitidine can improve OS in higher‐risk MDS and AML without requiring CR5, 7, 8, 9, 37; the effect of CC‐486 on OS has not yet been reported and was not captured in this phase 1 study, but is under investigation in an ongoing phase 3 trial of CC‐486 in patients with MDS (NCT01566695).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In total 7 patients with MDS or CMML and 2 patients with AML receiving CC‐486 monotherapy in this study attained CR or PR, including, importantly, patients for whom previous DNMTi therapy had failed. While multiple studies have shown injectable azacitidine can improve OS in higher‐risk MDS and AML without requiring CR5, 7, 8, 9, 37; the effect of CC‐486 on OS has not yet been reported and was not captured in this phase 1 study, but is under investigation in an ongoing phase 3 trial of CC‐486 in patients with MDS (NCT01566695).…”
Section: Discussionmentioning
confidence: 99%
“…Since approval for treatment for MDS in 2004,31 parenteral azacitidine has been shown to induce remissions and HI in a range of settings, from first‐line treatment of higher‐risk MDS, CMML and AML to maintenance therapy after alloHSCT 5, 6, 7, 12, 19, 20, 32, 33, 34. CC‐486, is an oral drug formulation of azacitidine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations